Signaling intact membrane-bound IL-15 enables potent anti-tumor activity and safety of CAR-NK cells - Xu, Xiaodi; Cao, Peiyu; Wang, Meng; Wan, Yan; Sun, Shuwen; Chen, Yuxin; Liu, Yilin; Su, Tong; Gao, Ge; Liu, Xinze; Zhong, Weixiang; Chen, Xi; et al. (Frontiers in Immunology, 2025)
BackgroundChimeric antigen receptor (CAR)-NK cells are a promising and safe alternative to CAR-T cells. However, the limited persistence in vivo restricts their clinical application and sustained therapeutic responses. IL-15 has been extensively used to improve CAR-NK cell persistence and effectiveness. Nevertheless, accumulation of IL-15 might induce uncontrolled proliferation of CAR-NK cells and thus lead to fatal side-effects. Therefore, it is essential to develop a safe and effective alternative strategy to improve the persistence and anti-tumor activity of CAR-NK cells.MethodsA signaling intact membrane-bound IL-15 (mbIL-15) was designed by fusing IL-15 and full-length IL-15Rα and was systematically compared with secretory IL-15 (sIL-15) in a B7H3-targeting CAR-NK cell system regarding their functionality and safety through various in vitro and in vivo experiments.ResultsBoth expression of sIL-15 or mbIL-15 significantly enhanced the proliferation by activating STAT5 and improved anti-tumor activity of CAR-NK cells in vitro and in vivo. Although CAR-NK cells with sIL-15 quickly eliminated intraperitoneal ovarian cancer, the mice experienced severe consequences, including dysregulated CAR-NK cell expansion, intense inflammatory responses, and irreversible organ damages. In contrast, CAR-NK cells carrying mbIL-15 showed moderate cell proliferation and potent tumor killing activity without observable adverse effects in both local treatment and systemic administration models.ConclusionHead-to-head comparative studies demonstrated that signaling intact mbIL-15 significantly improved therapeutic efficacy and safety of CAR-NK cells compared to sIL-15, which provided preclinical evidence for future clinical development.